The Impact of Using Voice of America (VOA) in Teaching Degree Comparison to Indonesian Junior High School Students - Fatima Ayu Ajzahra; Abdul Muin; Tatu Siti Rohbiah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This research was conducted based on the main problem is the learning effect of using the voice of America (VOA) YouTube Channel in Degree of Comparison. Based on the main problem formulated above, the research objectives are as follows: to determine the effect of using Voice of America (VOA) learning english YouTube Channel in teaching degree of comparison in the eighth grade of SMPN 24 Kota Serang. The subject of this study involved 60 students as a sample from class VIII SMPN 24 Kota Serang in 2022 as a population. The show that the value of t0 is 3.26 with degrees of freedom (df) is 58. There was a significant difference between students' understandings on degree of comparison Using Voice of America (VOA) English learning through YouTube Channel. The study found that most of the data showed an increase in learning using YouTube video channels. It is suggesting that students should consider the learning method used to achieve sustainability.